Pro-inflammatory S100A11 is elevated in inflammatory myopathies and reflects disease activity and extramuscular manifestations in myositis - Andrés Cerezo, Lucie; Hulejová, Hana; Šumová, Barbora; Kropáčková, Tereza; Kryštůfková, Olga; Klein, Martin; Mann, Heřman F; Zámečník, Josef; Pecha, Ondřej; Pavelka, Karel; Vencovský, Jiří; Šenolt, Ladislav (Cytokine, 2019)
BACKGROUND: S100A11 (calgizzarin), a member of the S100 family, is associated with oncogenesis, inflammation and myocardial damage. Our aim was to analyse S100A11 in idiopathic inflammatory myopathies (IIMs) and its association with disease activity features and cancer development. METHODS: S100A11 in muscle was determined by immunohistochemistry in polymyositis (PM), dermatomyositis (DM), myasthenia gravis (MG) and in subjects without autoimmune inflammatory disease (HC). S100A11 in plasma was measured in 110 patients with IIMs (PM, DM, and cancer associated myositis (CAM) patients) and in 42 HC. Disease activity was assessed by myositis disease activity assessment (MYOACT), muscle enzymes and C-reactive protein (CRP) were measured by routine laboratory techniques; autoantibodies by immunoprecipitation or by immunoblot. RESULTS: We observed an accumulation of S100A11 in the cytoplasm of regenerating and necrotizing muscle fibres of PM and DM patients. S100A11 was increased in plasma of all myositis patients compared to HC (3.8 (1.5-16.8) vs 2.8 (1.7-11.2) ng/ml, p = 0.011) and in DM and CAM patients compared to HC (4.0 (2.2-14.9) and 4.5 (1.5-9.1) vs 2.8 (1.7-11.2) ng/ml, p < 0.001 and p = 0.022, respectively). In all myositis patients, S100A11 correlated with the levels of lactate dehydrogenase (r = 0.256, p = 0.011), aspartate aminotransferase (AST) (r = 0.312, p = 0.002), CRP (r = 0.254, p = 0.022) and MYOACT (r = 0.245, p = 0.022). S100A11 was associated with MYOACT (r = 0.377, p = 0.030) and pulmonary and cutaneous disease activity in DM patients (r = 0.408, p = 0.017 and r = 0.417, p = 0.01, respectively). S100A11 was related to the levels of AST (r = 0.412, p = 0.027) in PM and to the levels of creatine phosphokinase (r = 0.432, p = 0.028) in CAM patients. CONCLUSIONS: We show for a first time a potential implication of S100A11 in the local inflammatory and tissue remodelling processes in myositis and an association of circulating S100A11 with disease activity and extra muscular manifestations in DM.
Keywords: dospělí; Female; C-Reactive Protein; Adult; Autoimmune Diseases; ženské pohlaví; S100 Proteins; lidé; S100 proteins; Disease activity; Aged, 80 and over; Inflammation; Humans; autoimunitní nemoci; kosterní svalová vlákna; Male; Muscle Fibers, Skeletal; Polymyositis; polymyozitida; Aged; Autoantibodies; Myositis; proteiny S100; lidé středního věku; C-reaktivní protein; senioři nad 80 let; senioři; mužské pohlaví; Calgizzarin; Middle Aged; autoprotilátky